Direct measurement of the mass difference between top and antitop quarks - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Arov, M.; et al. (American Physical Society (APS), 2011)
We present a direct measurement of the mass difference between top and antitop quarks (Δm) in lepton+jets tt̄ final states using the matrix element method. The purity of the lepton+jets sample is enhanced for tt̄ events by identifying at least one of the jets as originating from a b quark. The analyzed data correspond to 3.6fb-1 of pp̄ collisions at √s=1.96TeV acquired by D0 in Run II of the Fermilab Tevatron Collider. The combination of the e+jets and μ+jets channels yields Δm=0.8±1.8(stat)±0.5(syst)GeV, which is in agreement with the standard model expectation of no mass difference. © 2011 American Physical Society.